Covid-19 morbidity and outcomes among the patients observed in the pulmonary hypertension reference center. (14th October 2021) - Sirenko, Y; Zhyvilo, I; Radchenko, G
Abstract: Background: Pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTEPH) are progressive condition with high mortality rate despite modern pharmacotherapy. There is no reliable data concerning influence of Covid-19 infection on PAH and CTEPH morbidity and mortality. Aim: To evaluate influence 12-month Covid-19 pandemic presence on morbidity and mortality in patients with PAH and CTEPH observed in PH reference center. Methods: During the 12 months (from March 2020 to March 2021) we closely follow-up the condition of 404 initially alive patients with on PAH and CTEPH with specific PH therapy who were observed in our reference center for adults. All information was checked and confirmed with proper medical documents and Covid-19 diagnosis was confirmed with positive PCR or/and serological tests. We finished our database with the vaccination beginning. Results: Main data are presented in table. Among 404 patients symptomatic Covid-19 infection was documented in 44 (10, 9%) cases. Only 9 (20, 5%) of them were hospitalized because this reason, 4 patients of them (9, 1% from all Covid-19 diagnosis and 44, 4% from hospitalized) needed ICU because severe circulatory and respiratory failure. All of them needed the ventilator support. Unfortunately, despite of the necessary measures all of the ICU admitted patients died shortly during couple of days (mean 2, 5±1, 8). There was no difference in demographic, diagnosis and initial condition between hospitalized and ambulatory treated patients. The small numbers of died patients did not allow to make any statistically significant assumption. Conclusion: During 12-months Covid-19 pandemic presence 11% of PAH and CTEPH patients had symptomatic COVID-19 infection, roughly 20% of them needed hospital admission and 10% needed ICU and ventilator support. The mortality in ICU was 100%. FUNDunding Acknowledgement: Type of funding sources: None.